Antioxidant Activity, Phenolic, and Total Flavonoid Value of Balinese Trengguli Flower (Cassia fistula) - Harditya, Kadek Buja (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The Balinese trengguli flower (Cassia fistula), found in the northern part of Bali, is known to contain flavonoids and phenols, one of the sources of natural antioxidants that can reduce the effects of free radicals. This study aimed to extract the powder of trengguli flower with ethanol and measure the total flavonoids and phenolics. Furthermore, the antioxidant activity of the ethanol extract of Trengguli flower (EEBTF) was investigated. The filtrate was concentrated with a rotary evaporator after soaking the Trengguli flower powder in ethanol. Total phenolic and flavonoid levels were measured using UV-Vis spectrophotometry. Diphenyl-1-picrylhydrazyl (DPPH) technique was used to determine antioxidant activity. This study shows that Balinese trengguli flower extract has the highest antioxidant activity for a concentration of 100 mg/L with a DPPH radical inhibition percentage value of 87%. In this research, the ethanol extract of the Balinese trengguli flower has secondary metabolites of flavonoids and phenolics. The ethanol extract of Balinese trengguli flower has a flavonoid content of 8.35 mg QE/g and a total phenolic content of 8.12 mg GAE/g.